Interest, Understanding, and Behaviour: Conceptualizations of Sexuality Education for Individuals with an Autism Spectrum Disorder Using a Socially-Inclusive Lens - Gougeon, Nathalie A. (Université d'Ottawa / University of Ottawa, 2013)
Research shows that there is a gap between interest and experience in the area of sexuality for individuals with autism. Also, although these individuals have unique learning requirements pertaining to their sexuality, there is no consensus on the provision and content of such education. Using a socially inclusive theoretical lens founded on existing models of disability and competence, this bilingual study (a) developed a conceptual framework of sexuality education, as understood by adolescents living in Ontario with a diagnosis of high-functioning autism and their caregivers; (b) used extant texts to support the conceptualization provided by youth and caregivers; and (c) identified personal strengths and barriers, as well as societal supports and barriers that impact sexuality education for these youth. Using a qualitative orientation, this study employed in-depth interviews, surveys, and a literature review to better understand the topic under investigation. Twenty participants from 8 families took part in these interviews, including 9 adolescents and 11 caregivers. Survey and extant textual-analysis data were used to support the findings. Sexuality education content was conceptualized as a combination of facts and sociosexual norms, with emphasis on outcomes. Additionally, safety and pleasure were identified as important content areas, including the historically absent aspect of shared enjoyment. Some content areas were part of a greater discourse of normalization. Sexuality education was seen as a combination of formal and informal activities that are developmentally appropriate, proactive, and take place across various settings and groupings. Caregivers were cited as the primary providers of informal education, whereas schools and other community partners were seen as formal providers of education. Various supports and barriers were identified, some of which were viewed as both. Themes related to media and technology pervaded all findings. This study provides further emic and etic understanding of the subject with implications for practice, policy, and theory.
Keywords: high-functioning autism; Asperger syndrome; sexuality education; social inclusion